The Utility of Diffusion-Weighted MRI Lesions to Compare the Effects of Different Heparinization Schemes in Intracranial Aneurysms Treated by Endovascular Intervention - Zhang, Linfeng; Zhou, Xiaobing; Liu, Yong; Ding, Cong; Wang, Yang; Yang, Hongchao (Frontiers in Neurology, 2020)
Endovascular treatment has become the main treatment method for intracranial aneurysms, but ischemic complications are the main risk of endovascular treatment 1. Diffusion-weighted imaging (DWI) is a sensitive method for detecting acute ischemic strokes. Studies have found that the incidence of ischemic lesions is between 10% and 77% after endovascular treatment of intracranial aneurysms, and ischemic lesions may be associated with cognitive decline, depression and future stroke in patients2-5. The causes of these associations of ischemic lesions include fragile plaques, thrombosis exfoliation in aneurysms, and thrombosis caused by the catheter6. Previous studies have also shown that age, aneurysm size, and use of complex embolization techniques are risk factors for ischemic complications7,8. Heparinization is an important method to prevent ischemic complications; however, there is no unified scheme for heparinization. The commonly used schemes are systemic heparinization and local heparinization. The goal of this study is to apply DWI to evaluate the effects of different heparinization schemes on intracranial aneurysms with endovascular treatment.